2022-RA-1540-ESGO MITO 25.1: a randomized, molecular driven phase II trial of carboplatin-paclitaxel-bevacizumab vs carboplatin-paclitaxel-bevacizumab-rucaparib vs carboplatin-paclitaxel-rucaparib, selected according to HRD status, in patients with advanced (Stage III B-C-IV) ovarian, primary peritoneal and fallopian tube cancer. (20th October 2022) - Musacchio, Lucia; Salutari, Vanda; Pignata, Sandro; Valabrega, Giorgio; Zavallone, Laura; Cormio, Gennaro; Mosconi, Anna Maria; Giolitto, Serena; Giudice, Elena; Ricci, Caterina; Zamagni, Claudio; Nero, Camilla; et al.
Abstract : Introduction/Background: Poly (ADP-ribose) polymerase (PARP) inhibitors alone and in combination with Bevacizumab have shown significant clinical benefit as maintenance therapy in women with newly diagnosed ovarian cancer (OC) regardless BRCA mutational status and in homologous-recombination deficiency (HRD) positive patients, respectively. However, despite the remarkable improvements in the therapeutic algorithm of OC disease over the years, the best first line treatment is still controversial. Methodology: MITO 25.1 is a multicenter, randomized open-label, phase II study comparing Carboplatin-Paclitaxel-Bevacizumab vs Carboplatin-Paclitaxel-Bevacizumab-Rucaparib vs Carboplatin-Paclitaxel-Rucaparib.Eligible patients, with histological confirmed high grade serous or endometrioid advanced OC, will be randomized in a 1:1 ratio according to HRD status. Results: HRD negative patients: ARM A: Carboplatin AUC 5 + Paclitaxel 175 mg/m2 q 21 + Bevacizumab 15 mg/kg for 5 cycles (starting from cycle 2) followed by Bevacizumab 15 mg/kg q 21 for 17 cycles, ARM B: Carboplatin AUC 5 + Paclitaxel 175 mg/m2 q 21 for 6 cycles followed by Rucaparib 600 mg BID q 28 for 24 cycles as maintenance HRD positive patients: ARM B: Carboplatin AUC 5 + Paclitaxel 175 mg/m2 q 21 for 6 cycles followed by Rucaparib 600 mg BID q 28 for 24 cycles as maintenance: ARM C: Carboplatin AUC 5+ Paclitaxel 175 mg/m2 q 21 + Bevacizumab 15 mg/kg for 5 cycles (starting from cycle 2) followed by Bevacizumab 15 mg/kg q 21 days for 16 cycles + Rucaparib 500 mg part BID q 28 for 24 cycles as maintenance Conclusion: The primary endpoint will be PFS. The secondary endpoints will be overall survival (OS), PFS2, adverse events according to CTCAE 5.0 and patient-reported outcome. Patients recruiting started in March 2021. To date, 159 of the 300 patients planned have been enrolled.